Peningkatan Kapasitas Kelompok Ibu PKK Desa Situ Udik melalui Pembuatan Kompos Limbah Rumah Tangga - Hikmah Zikriyani; Dewi Juliah Ratnaningsih; Elizabeth Novi Kusumaningrum; Venty Fitriany Nurunisa; Arie Aryanto; Na’ilah Insani Alifiyah; Faujatul Hasanah; Nurul Nisa'a Amin; Mukhammad Rozaq Sutoni; Restu Para Ratu (I-Com: Indonesian Community Journal, 2025)
Situ Udik Village faces household waste issues due to population growth and changing consumption patterns, leading to environmental pollution. The 2024 National Community Service Program by Indonesia Open University aims to address this problem by utilizing organic waste as compost to enhance agricultural productivity. The methods include expert-led socialization, compost-making training, and the application of simple technology using buckets as composters. The composting process involves burned rice husks, rice bran, and household organic waste, which are fermented for 21 days (about 3 weeks). The results indicate that the produced compost has a neutral pH and optimal fertility for use as a planting medium. This program not only reduces waste but also improves soil fertility and enhances community welfare through new economic opportunities. Moving forward, research will focus on analyzing the chemical composition of the planting medium and its impact on agricultural productivity. Keywords: Situ Udik Village, Compost, Household Waste